Experimental and numerical studies of pin-ended press-braked S960 ultra-high strength steel channel section columns - Wang, Fangying (2022)
Grade S960 ultra-high strength steel is receiving increasing attention owing to its excellent strength-to-weight ratio. However, its application in construction engineering is rather limited due to the lack of adequate design rules, as the current established codes in Europe, North America and Australia/New Zealand only cover the design of steel components with material grades up to S700 (or S690). This prompts investigations into different types of S960 UHSS structural components and development of accurate and efficient design rules for them. The present paper focuses on press-braked S960 UHSS channel section columns prone to flexural buckling about the minor principal axes, with their behaviour and resistances thoroughly examined through experiments and numerical modelling. An experimental programme was firstly performed on two non-slender press-braked channel sections, with five column specimens of varying member lengths employed for each cross-section, and included initial global and local geometric imperfection measurements and pin-ended column tests about the minor principal axes. This was followed by a parallel numerical modelling programme, where finite element (FE) models were developed to simulate the experimental results and afterwards adopted to perform a parametric study to generate additional numerical data over a broader spectrum of cross-section dimensions and member lengths. It is worth noting that there were two orientations associated with minor-axis flexural buckling of press-braked S960 UHSS channel section columns, namely ‘C’ orientation (indicating that columns buckled towards the webs) and ‘reverse C’ orientation (indicating that columns buckled towards the flange tips), and both of the two types of failure modes were carefully examined in the present study. It was found that channel section columns failing by flexural buckling in the ‘reverse C’ orientation generally exhibited superior resistances relative to their counterparts with failure in the ‘C’ orientation. The experimental and numerical data were also used to assess the applicability of the codified provisions for press-braked S700 (or S690) channel section columns failing by flexural buckling about the minor principal axes to the design of their S960 counterparts. The assessment results indicated that (i) the existing European code leads to overall conservative and scattered design flexural buckling resistances, especially for those relatively short and intermediate press-braked S960 UHSS channel section columns with failure in the ‘reverse C’ orientation, and (ii) the North American specification and Australian/New Zealand standard result in a higher degree of design accuracy and consistency than the European code, but with many over-predicted flexural buckling resistances for press-braked S960 UHSS channel section short and intermediate columns failing in the ‘C’ orientation.